Dancing with Reggio Emilia: Metaphors for quality - Giamminuti, Stefania (Pademelon Press, 2013)
Stefania Giamminuti spent six months researching in the municipal infant-toddler centres and schools of Reggio Emilia, Italy. Her unique experiences are vividly recounted in this rich book, with its seductive images and lyrical storytelling drawing the reader into daily events in these world-renowned places for young children. The voices and contexts of children, teachers atelieriste, pedagogiste, and families in Reggio Emilia come alive in this important and impressive book—an invitation to encounter the beauty and complexity of this exceptional social and cultural projects of early education. Stefania proposes a new key for interpreting the educational project of Reggio Emilia in international contexts by exploring the ‘local values’ that emerged through her observation of life in Nido Arcobaleno and Scuola Pablo Neruda and relating these to ‘connective values’ to inform the philosophy, policy and practice of early childhood education and care internationally. Stefania engages with the construct of ‘quality’ in early childhood education and care, proposing new approaches to theorising quality as a metaphor and complex cultural and value-laded construct.